An Approach to Clinical Magnetocardiology - AWANO, IMASU; MURAMOTO, ATSUKO; AWANO, NAOYUKI (The Tohoku Journal of Experimental Medicine, 1982)
AWANO, I., MURAMOTO, A. and AWANO, N. An Approach to Clinical Magnetocardiology. Tohoku J. exp. Med., 1982, 138 (4), 367-381-Magnetocardiograms (MCGs) of normal human subjects and patients with various heart diseases and of fetuses (fetal magnetocardiogram, FMCG) were recorded using a SQUID magnetometer with a built-in second derivative gradiometer in a magnetically unshielded environment. MCGs and ECGs in this study were taken simultaneously at the same precordial chest positions (V1-V6). The following results were obtained: (1) The waves of MCG showed a variety of changes which can never be detected in ECGs. (2) Clear FMCGs could be recorded without being overlapped by MCG of the mother. (3) In MCGs from a patient with complete A-V block, there was a secondary pacemaker spike which was presumably related to ventricular depolarization. (4) There were two kinds of characteristic changes with time in MCGs after onset of anterior myocardial infarction, which could be confirmed in experiments with dogs. Thus, the results obtained so far indicate a bright future of magnetocardiology in clinical medicine.